Peran perpustakaan dalam mendukung World Class University - Sri Endah Pertiwi; Suwondo Suwondo; Lis Setyowati (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
ABSTRACT UPT Perpustakaan Undip invited public and private university libraries in Semarang to discuss and support World Class University (WCU). The library has quality academic resources, supports learning and research, maintains access to information, improves the reputation of the University, and provides access to quality education, so universities really need libraries to achieve international standards. The research objectives in this Focus Group Discussion (FGD) are (1) to understand librarians' reflections in relation to WCU. (2) Exploring new ideas supporting a world-class university's achievement. The method used in the research is a qualitative approach with the implementation of Focus Group Decision (FGD). This research focuses on two components: reflection and exploration of new ideas. In the discussion forum, the focus was on the objectives, activity programs, obstacles, and efforts to overcome the obstacles in these two components. The FGD participants are librarians who are members of FKP3U (Forum Komunikasi Pustakawan dan Pengelola Perpustakaan Undip) within the Diponegoro University environment and librarians from higher education institutions in Central Java, totaling 80 people. Then, the participants were divided into 5 (five) groups and led by a moderator to discuss two components with 12 WCU segments. Reflection on global ranking achievements with information literacy training, open access policies, repositories, and promotion. Exploration of new ideas for achieving global rankings through citation literacy training, information repackaging, the establishment of data and analysis centers, and interdisciplinary research collaboration Keywords: exploration of new ideas ; reflection ; university ; World Class University